Hubungan Kontribusi Lauk Hewani, Nabati dan Sayuran dengan Tingkat Konsumsi Protein dan Zat Besi pada Mahasiswi yang Tinggal di Rusunawa Residence 1 Unimus - Septia Dewi Arianti; Agustin Syamsianah; Erma Handarsari (Universitas Muhammadiyah Semarang, 2015)
Anemia is a lack of blood diseases are mostly caused by the consumption of food, thats less of iron. Lack of iron consumption in Indonesia caused by the people consume more plant foods that are less of iron, more less than the animal foods that are high of iron, The condition is very risky tothe occurrence of anemia. The protein consumpsion of Indonesian community are still low. The condition will increase the risk of occurence of anemia.The general objective of this study was to determine the relationship between contribute a side dish of animal, vegetable and vegetable with protein and iron consumption levels of the student who lives in Rusunawa Residence 1 UNIMUS.This research is explanatory research design with cross sectional approach. The number of sample is 52 students who are living in Rusunawa Residence 1 UNIMUS. The sample was put bythe simple random sampling tehnique. The bivariate statistical analysis was done by the Pearson correlation test.The results show that the average of contribution of protein animal dishes was 12.68% of AKG and the average of iron was 4.62% of AKG, The average of contribution of protein vegetableside dishes was 36.92% of AKG and the average iron was 40.76% of AKG. The average of protein vegetable contribution was 4.82% of AKG and iron was 6.36% of AKG. There are 29 student (55,8 %) who consume protein under 100% of AKG and there are 48 student (92,3 %) who consume iron under 100% of AKG.Conclusion : There is no relationship between the contribution of protein and iron animal side dish with the protein and iron consumption level. There is a correlation between thecontribution of protein and iron vegetable side dish with the protein and iron consumption levels.Keywords: The Contributions of Side Animal, plant and Vegetables. , The Protein and Iron Consumption Level.